The teaching of Visual Arts and the inclusion process of adolescents with autism spectrum disorder: reality and perspectives (Research, Society and Development, 2020)
Currently, we live in a world that changes are generated by the advancement of knowledge of technology and communication, which challenges us in the most diverse areas of relationship with human beings. In this context, this study aimed to discuss the reality and perspectives of teaching visual arts and the inclusion process of adolescents with autism spectrum disorder. This is a bibliographic search with exploratory procedures. For the construction of this study, scientific articles published in databases such as SciELO, Lilacs, Google Escolar were used as data sources, in addition to official websites, and books that discuss the theme investigated. After obtaining the material, an exploratory reading of the bibliographic works was carried out, with the objective of verifying which the contents of the articles consulted were related to the research. Finally, an interpretative reading was carried out in which it sought to give a greater meaning to the results achieved with the analytical reading. It was observed that the context of inclusion in Brazil, in spite of the various changes that the legislation has undergone over the years, is still embryonic, and that much needs to be discussed and executed, in order to better the conditions of the insertion of students with autism in the context of inclusive regular school. In art classes, this reality is no different, since many teachers are not prepared to work with students with autism spectrum disorder, as they do not invest in research, much less in teacher education and training to deal with this population, in addition to the lack of investment in school infrastructure and material resources.